(untitled) (Annals of Medical Research, 2021)
Aim: Leptin activates multiple intracellular signaling pathways, including JAK/STAT, by binding to its receptor. Leptin is also an important regulator of glucose homeostasis. Although both glucose and leptin increase breast cancer cell proliferation in vitro, whether the enhancing effect of glucose on the proliferation of breast cancer cells is mediated by the leptin signaling pathway is not known. The aim of this study was to investigate the effect of different glucose concentrations on the leptin signaling pathway in MCF-7 and T47D breast cancer cells.Material and Methods: MCF-7 and T47D cell proliferation in different glucose concentrations (2.5 mM, 5 mM, 25 mM, or 50 mM) were assayed using CCK-8 assay. Leptin, leptin receptors (ObR, ObRb) as well as STAT3 mRNA and protein levels in both cell lines in different glucose concentrations were examined by RT-PCR and western blot, respectively.Results: Incubation in 2.5 mM, 5 mM, 25 mM, or 50 mM glucose for 72h significantly increased the proliferation of both MCF-7 and T47D cells compared to 0 mM glucose incubated cells (P0.05). However, ObR protein levels in MCF-7 cells incubated in 25 mM glucose was significantly lower compared to 0 mM glucose by western blot (p0.05). Conclusion:Our data suggest that the enhancing effect of glucose on breast cancer cell proliferation is not mediated by the JAK/STAT pathway.